PERENCANAAN JALUR GANDA KERETA API KORIDOR SEMARANG BOJONEGORO RUAS SEMARANG TAWANG – NGROMBO - Dian Rachmasari; Srie Heruyani Stevia Lukmanasari; Bambang Pudjianto; Moga Narayudha (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Along with the increasing demand and growth of population, the more necessary a good transportation to smooth traffic flow. Especially KA demands will increase service capacity, speed, and safety and comfort, it is necessary to thinking or planning that address these issues, including the improvement of facilities and infrastructure such as the construction of double track Railway network. In this case only a segment of Semarang Tawang Railway track-Ngrombo are supposed to represent the path Bojonegoro Semarang. Stages of the methodology used in the planning stage consists of the problem formulation, literature review, data collection, data analysis, planning, RAB and the final stage. The change capacity plans that will be served by this pathway, leading to the condition of the existing track alignment and structure must be adapted to the requirements for Class I. path Based on the soil conditions on the project which is unstable and track existing conditions that are often submerged rob the new double track line is designed with a higher elevation than the existing track conditions. From the analysis it can be seen that almost all double track line has a condition that is much different from the existing track in terms of structural, alignment and land protection. Calculation results obtained from this project spent Rp 457.000.000.000,00 to build the new track.